Bifunctional Electrocatalysts: Self‐Anti‐Stacking 2D Metal Phosphide Loop‐Sheet Heterostructures by Edge‐Topological Regulation for Highly Efficient Water Oxidation (Small 7/2021). Issue 7 (18th February 2021) - Quan, Quan; Lai, Zhengxun; Bao, Yan; Bu, Xiuming; Meng, You; Wang, Wei; Takahashi, Tsunaki; Hosomi, Takuro; Nagashima, Kazuki; Yanagida, Takeshi; Liu, Chuntai; Lu, Jian; et al.
Abstract : 2D metal phosphide loop‐sheet heterostructures are controllably synthesized by edge‐topological regulation, where Ni2 P nanosheets are edge‐confined by the N‐doped carbon loop containing ultrafine NiFeP nanocrystals. In article number 2006860, Johnny C. Ho and co‐workers report that the loop‐sheet feature with lifted‐edges can prevent the self‐stacking of 2D nanosheets and induce accessible open channels for catalytic site exposure and charge carriers/mass transfer, resulting in a remarkable oxygen evolution activity.